A escrita do texto acadêmico na graduação: modos de utilização de conceitos teóricos de uma área de conhecimento - Vieira, José Antônio (2013)
In this study we have developed a discussion about academic text production in the undergraduate course of Literature and Languages. Specifically, we are going to analyze the monographic text writing in order to verify the meaning effects created from the ways of showing other s discourses that constitute a written production. As a means to do that, we are going to answer the following question: How does a young researcher make use of a theory in order to be part of a particular scientific community? We aim to: 1) analyze the linguistic resources, like quotations and signs of cohesion that demonstrate the other s voice presence in academic writing; 2) observe the meaning effects produced through the ways that the one who writes shows the other s voice in the written text. Firstly, we have selected 23 (twentythree) monographs produced in the last five years by students from a Literature and Languages undergraduate course in a determined public university. However, in this study, we have analyzed just 02 (two) different monographic texts. To develop such an investigation, we have inquired Kuhn s concept of science, which shows the existence of different meanings of science production in the course of the centuries. It allows us to define academic writing as science production that develops and contributes to knowledge production. With the purpose of restricting the meaning of writing conception, we have relied on Coracini, who assumes that all writing production is the registration of the self, in other words, writing comes from the subject s intervention, it is to say that only an imposition of the self guarantees the subject as author of what he writes. We have as theoretical basis the following concepts: 1-) Authier-Revus s enunciative heterogeneity, that allowed us to analyze the written marks of the other in the monographic writing; 2-) Pêcheux s reformulation-paraphrase and Orlandi s polysemy and paraphrase, concepts that present notions of productivity and creativity as ways of meaning production, and allows us to observe how the process of language production in academic writing is established; 3-) Rossi-Landi s concept of exchange-value and use-value, which consider language as a linguistic work, allowing us to verify the differences between use and social functionality in a determined theory; and 4-) Possenti s notion of authorship indicia, with which we have identified attitudes that make the one who writes author of his own text. We have verified that writing characterized for repetition and reproduction may develop a meaning effect that constructs the idea that writing production promotes an author, a concept or a theory. We have also realized that a written text that restricts itself to reproduce other authors discourses and does not articulate a theory with data analysis or with work methodology, when evaluated is approved and legitimates itself as scientific production. That demonstrates the existence of academic productions that do not develop any functionality of the employed theory. The text works as a means to promote its theoretical concepts, and theory. It is to say that the theoretical foundantion, which usually is a way to argue and sustain scientific production, does not have any function. Thus, we consider that the way someone shows the other s discourse in academic writing may work as a way to underline what the other asserts to the detriment of the researcher s words. This fact allows us to comprehend that a way of writing may evidence a meaning effect of the author s, theory s or theoretical concepts promotion